A divisão social do trabalho na indústria da segurança privada - Santos Filho, Cássio da Silva (2021)
The research analyzes the phenomenon of the Social Division of Labor in the Private Security Industry. From the Marxian perspective, the concepts of Social Division of Labor, Merchandise Fetish, Industry, productive work and Private Security are operationalized. The analysis is critical and dialectical, and has the capitalist mode of production as a macroeconomic scenario, mainly since the advent of Neoliberalism. It is understood that the Social Division of Labor is an assumption in Capitalism and has intensified in it, characterizing this system. The large industry, inserted in this process, has the Division of Labor as an intrinsic part of its gear. From the realization that Private Security makes up an Industry, the hypothesis was built that, in this sector, the Social Division of Labor is already sufficiently developed to potentiate important socioeconomic impacts. The main question raised is: what is the socioeconomic implication caused by the Division of Labor in the Private Security Industry? The method used is Historical Dialectical Materialism and the main methodological procedures adopted were: bibliographic research and descriptive statistics. The initial time frame of the historical analysis of the legislation is the 1960s, in a broader perspective; and with empirical data from the years 2010 in Brazil. The main indicators analyzed were: number of companies; revenue and the evolution of workers' remuneration. These and other indicators showed an advance of private capital in the Security Industry in Brazil. The analysis of the relationship between the Social Division of Labor and the Private Security Industry is of fundamental importance, with implications that alter the social dynamics, as observed in this work: changes in the dynamics of the labor market, precarious workforce and consumption of security merchandise by the state.